(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
In this paper I review some apparent contradictions between Iberian and Celtiberian epigraphic practices, like the confusion between some variants of the ta and the bo signs in Cortono’s bronze, the distinction of simple and complex variants of the ke sign in Luzaga’s bronze, and the role of the m sign at the origin of the eastern Celtiberian script. Although the falera from Armuña, an eastern dual inscription from the third century BC, has clarified many aspects regarding the origin of the Celtiberian dual system, some doubts remain. This work also defends the double Iberian origin of the two variants of Celtiberian writing and the non-intervention of Latin writing in the origin of redundant Celtiberian writing, since it is almost completely dual and western.